2021
DOI: 10.5334/joc.198
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Memory Updating: State Dependency vs. Reconsolidation

Abstract: Reactivating a memory trace has been argued to put it in a fragile state where it must undergo a stabilization process known as reconsolidation. During this process, memories are thought to be susceptible to interference and can be updated with new information. In the spatial context paradigm, memory updating has been shown to occur when new information is presented in the same spatial context as old information, an effect attributed to a reconsolidation process. However, the integration concept holds that mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…If there is a mismatch, memory updating will not be found. Evidence in support of this idea has been found in nonhuman animals (Gisquet-Verrier et al, 2015 ) and humans (Kiley & Parks, 2022 ). Despite that support, the current data are challenging because one tenet of the integration account is that memory updating is a rapid process that does not require a delay between Day 2 reactivation and the final test (see Bridge & Voss, 2014 , for an example in a different paradigm).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…If there is a mismatch, memory updating will not be found. Evidence in support of this idea has been found in nonhuman animals (Gisquet-Verrier et al, 2015 ) and humans (Kiley & Parks, 2022 ). Despite that support, the current data are challenging because one tenet of the integration account is that memory updating is a rapid process that does not require a delay between Day 2 reactivation and the final test (see Bridge & Voss, 2014 , for an example in a different paradigm).…”
Section: Discussionmentioning
confidence: 86%
“…There are challenges to the reconsolidation theory, though (Capelo et al, 2018 ; Gisquet-Verrier et al, 2015 ; Gisquet-Verrier & Riccio, 2018 ; Kiley & Parks, 2022 ; Klingmüller et al, 2017 ; Sederberg et al, 2011 ), most of which argue that the memory updating found in Hupbach et al’s ( 2007 ) paradigm is attributable to context-related retroactive interference or encoding specificity and not a distinct neurobiological process. However, these alternatives struggle to explain the time-dependent nature of memory updating (but see Sederberg et al, 2011 ).…”
mentioning
confidence: 99%